Utility of in vitro release testing (IVRT) to assess ‘sameness’ of 1% clotrimazole creams for use as a biowaiver - Hannah Wellington; Seeprarani Rath; Sagaran Abboo; Isadore Kanfer (AAPS Open, 2023)
Abstract The October 2022 draft United States Food and Drug Administration (FDA) guidance presents an option of in vitro release test (IVRT) studies as a biowaiver for topical drug products submitted in abbreviated new drug applications (ANDAs). However, the product-specific guidance (PSG) for 1% clotrimazole (CLZ) topical cream does not provide an in vitro option for biowaiver and requires a clinical endpoint study to demonstrate bioequivalence (BE). Therefore, the main objective was to use IVRT to investigate pharmaceutical equivalence of several 1% CLZ topical creams from two countries — South Africa (SA) and Canada. This investigation aims at demonstrating the utility of IVRT to determine ‘sameness’ and/or differences between topical creams containing 1% CLZ and the potential of IVRT for supporting biowaivers, thereby obviating the necessity to conduct clinical endpoint studies in patients. A validated IVRT method was applied to conduct comparative IVRT runs on five generic products marketed in SA and one Canadian generic, which were compared against a relevant comparator product from their country of origin in accordance with the FDA’s acceptance criteria of 75–133.33%. All five SA-marketed generic creams showed pharmaceutical inequivalence to the SA comparator product indicating Q1/Q2/Q3 differences. Despite containing the same excipients as both comparator products, the Canadian generic showed substantially lower release rate compared to the comparator products which could be attributed to Q2/Q3 differences. The IVRT method displayed the requisite ability to assess the various 1% CLZ creams and confirmed the potential of the IVRT method to support a biowaiver for 1% CLZ topical creams. Graphical Abstract